2018
DOI: 10.1089/tmj.2017.0190
|View full text |Cite
|
Sign up to set email alerts
|

User Experience of an Innovative Mobile Health Program to Assist in Insulin Dose Adjustment: Outcomes of a Proof-Of-Concept Trial

Abstract: The m-Health system for IDA showed promising levels of adherence, usability, perception of usefulness, and satisfaction. Further research is required to assess the feasibility and cost-effectiveness of using this system in outpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 38 publications
1
22
0
9
Order By: Relevance
“…In this feasibility trial, we evaluated the time-efficiencies and user experience of a newly developed mIDA service, following promising user feedback from an earlier proof-of-concept trial 11. The findings suggest that mIDA improves time-efficiencies by 54.8% from a CDE perspective, has the potential to reduce transcription error and improves the patient experience in the IDA service.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this feasibility trial, we evaluated the time-efficiencies and user experience of a newly developed mIDA service, following promising user feedback from an earlier proof-of-concept trial 11. The findings suggest that mIDA improves time-efficiencies by 54.8% from a CDE perspective, has the potential to reduce transcription error and improves the patient experience in the IDA service.…”
Section: Discussionmentioning
confidence: 99%
“…We did not report on adherence as it would be impossible to differentiate between the two approaches given a within-subject design. mHealth intervention trials have shown that the users improve glycaemic status in the short-term (up to 12 months)20 but reports regarding adherence are mixed and difficult to evaluate 11 21. As the IDA process usually lasts for a period of 4–6 weeks only, the service efficiency derived from mHealth strategies are likely to be sustainable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Para a temática DM também é possível encontrar alguns usos do e-health como por exemplo um medidor de glicose ativado por bluetooth para ajudar no ajuste diário de dose de insulina, apresentando índices satisfatórios de adesão e usabilidade pelos usuários (Ding et al, 2017). Ou até mesmo um telemonitoramento utilizado para controlar a glicemia das pessoas com diabetes.…”
Section: Benefícios Do E-healthunclassified